Keefektifan Teknik Disensitisasi Sistematis untuk Mereduksi Gangguan Kecemasan Sosial Santri di Madrasah Aliyah Negeri - Rasyadi, Ahmad Fitra; Hambali, IM; Indreswari, Henny (Buletin Konseling Inovatif, 2025)
Santri is required to be able to make social adjustments because they are in the same environment. Social problems will arise when students cannot adjust to the dormitory environment, resulting in non-achievement of social responsibility development tasks and disrupting students' academic activities. This study aims to determine the effectiveness of systematic desensitization techniques in reducing students' social anxiety disorder. The research method used was a single-subject study with the A-B-A1-B1 reversal design. The sampling technique used purposive sampling with the criteria of male and female students of class XI MAN, who had never participated in systematic desensitization therapy and were willing to participate in the entire series of counseling. The intervention used is a systematic desensitization technique. The data collection instrument used measuring social anxiety disorder and direct observation. Data analysis was performed by visually analyzing the data under and between conditions. The direction of the trend is analyzed using the split-middle method to obtain a more certain data measure by calculating the median value of each condition. The results of this study indicate that the systematic desensitization technique effectively reduces students' social anxiety disorder.